Da negatividade a positividade: possível trânsito de saberes, práticas e representações sociais sobre o estigma da hanseníase - Lima, Izabella Bezerra de (2012)
Leprosy is a chronic infectious-contagious disease, caused by Mycobacterium leprae, manifested by dermatological and neurological signs and symptoms and has great disabling power. It was marked by a strong stigma throughout its history, since its bearers represented a threat, target of fear and social contempt. Currently, leprosy has treatment and cure, and the need to separate the diseased from family and social environment is no more necessary. However, patients still suffer prejudice and discrimination. This study aimed to understand the social representations of leprosy that interfere modifying mental health of the patient with leprosy in relation to stigma and prejudice. This is a descriptive and exploratory study, with qualitative approach, which involved 22 users of the Special Care Clinic in Infectious Diseases at the Hospital Giselda Trigueiro, located in Natal / RN. They were in use of multidrug therapy in the period of data collection, were of both sexes, aged between 16 and 80 years of age and classified as paucibacillary or multibacillary. The study was approved by the UFRN Ethics in Research Committee. Data collection was performed by filling the questionnaire identification and then for conducting the semi-structured interview, which was recorded. After the end of data collection, there was the construction of tables and graphs, using the Microsoft Excel Start 2010 for proper characterization of the research subjects; and for the treatment of the data obtained from the interviews, was used the Content Analysis and based on the Theory of Social Representations. The subjects studied were mostly male (64%), married or in a stable relationship (68%), concentrated in the age group 50-60 years (36%) and 28-38 years (23%), had at most elementary education (65%) and were low-income (59%). Of the total respondents, 64% were classified as multibacillary, with predominantly dimorfous form, and 50% had disability grade I or II, with different periods of diagnosis. The reports originate two categories: 1. The negative meanings of illness and leprosy; and 2. The positive meanings of illness in leprosy, which were subsequently subdivided into subcategories. Thus, it was found that in the group studied, the social representation of leprosy experiences a moment of transition, as regards the understanding of the disease and its way of experiencing the disease process. Such representation is anchored in the quality of information on the disease of its bearers and aimed at an attempt to face the illness of leprosy as a "normal process". It was found in this study that the transition is due to the work of combating stigma and consequences of leprosy, which is able to gradually transform reality, both regarding the team work of reference, and in relation to a broader character, of actions of health education, which favors overcoming of psychosocial disabilities